Factors influencing the uptake of influenza vaccine vary among different groups in the hard‐to‐reach population. (26th February 2020) - Kong, Khai Lin; Chu, Sandy; Giles, Michelle L.
Abstract: Objective : This report describes a mobile outreach influenza immunisation program for vulnerable populations in a resource‐rich setting. It explores vaccine recipients' demographics, comorbidities and vaccination histories, and the factors influencing their decision to receive vaccine during outreach. Methods : Teams of nurse immunisers visited and provided influenza vaccines to clients from 21 sites (18 community centres for migrants, refugees and the homeless; and three outpatient clinics). Risk factors for severe influenza, vaccination histories and perceived barriers and facilitators to vaccines were collected from vaccine recipients. Results : A total of 1, 032 vaccine recipients participated in the survey with responses collected from April to October 2018. Of these, 54% reported at least one risk factor for severe influenza. Sixty per cent of recipients had not received an influenza vaccine in 2017, with most of them reporting 'not worried about influenza' as a reason. Pregnant participants most frequently reported a healthcare provider's recommendation as the reason to receive the vaccine. Conclusion : An outreach program comprising of a means of taking vaccines to the population was a successful strategy to deliver influenza vaccines to high‐risk populations. It needs to be considered in the full range of delivery models to improve influenza vaccine coverage, even in resource‐rich settings. Implication for public health : Strategies reaching out to vulnerable populations are crucial to maximise vaccine uptake.